Drought-Tolerant Soybean Seed Varieties: IPSR Innovation Profile - Chigeza, G. (2022)
Climate smart seeds of soybean, cassava and cowpeas are tolerant to many abiotic and biotic stresses such as drought, heat, pests and diseases, which results in stable productivity under challenging weather conditions. Through this work, we (i)l support NARS, SME seed companies, and community based out-grower partners to accelerate variety release and upscaling of seed production, (ii) develop and test innovative, evidence-based tools and strategies to improve women and youth entrepreneurs’ access to climate smart seed, accelerate varietal turnover; and expand seed marketing to women, youth and men farmers who are not reached by current seed value chains.; (iii) Promote the use of good agronomic practices (e.g. minimum tillage, rotations, mulching, etc) to enhance crop productivity; and (iv) improve access to technical information through training of extension staff and making seed production protocols available to users (farmers, extension and seed companies).